Accounting regulations, enforcement, and stock price crash risk: Global evidence in the banking industry. Issue 3 (December 2019) - Abedifar, Pejman; Li, Ming; Johnson, Dean; Song, Liang; Xing, Saipeng
Abstract: This study uses the banking industry as a unique testing setting to examine the impact of accounting and enforcement regulations on stock price crash risk. We find that stocks are less likely to crash in countries with stricter accounting regulations and enforcement standards. More importantly, we provide evidence that the impact of accounting regulations is more significant in countries with stricter enforcement standards, suggesting that enforcement mechanisms and accounting regulations are complementary. We find that the main channels for accounting regulations and enforcement standards to affect stock price crash risk are regulations that strengthen information disclosure and improve the effects of direct supervision and external auditors. Our findings are robust after we include more control variables, employ regional regulatory developments as instrumental variables, conduct change regressions, use alternative measures of enforcement, and estimate in various subsamples. Our study has policy implications for how to design accounting regulations and enforcement mechanisms in a more effective manner.